2014
DOI: 10.1007/s12028-013-9947-6
|View full text |Cite
|
Sign up to set email alerts
|

The FOUR Score and GCS as Predictors of Outcome After Traumatic Brain Injury

Abstract: FOUR is comparable to GCS in terms of predictive ability for functional status, cognitive outcome 3 months post-injury, and in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 31 publications
1
42
0
5
Order By: Relevance
“…In a study by McNett et al comprising 136 patients admitted to the ICU, the authors compared FOUR and GCS scores at 24 and 72 h for functional and cognitive outcomes, and also compared the scores at same time points with mortality [7]. The FOUR score was found comparable to GCS in terms of predictive ability for functional status, cognitive outcome at 3 months post-injury, and in-hospital mortality [7]. The AUCs for FOUR and GCS scores for predicting mortality were 0.913 and 0.935, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by McNett et al comprising 136 patients admitted to the ICU, the authors compared FOUR and GCS scores at 24 and 72 h for functional and cognitive outcomes, and also compared the scores at same time points with mortality [7]. The FOUR score was found comparable to GCS in terms of predictive ability for functional status, cognitive outcome at 3 months post-injury, and in-hospital mortality [7]. The AUCs for FOUR and GCS scores for predicting mortality were 0.913 and 0.935, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published study by Mc Nett et al, the authors found that the FOUR score is comparable to GCS in terms of predictive ability for functional status, cognitive outcome at 3 months post-injury, and in-hospital mortality [7]. In a similar study by Sadaka et al, the authors found that FOUR score was an accurate predictor of in-hospital mortality, and neurologic outcome.…”
Section: Introductionmentioning
confidence: 94%
“…Since its introduction in 2005, the FOUR score has been investigated against the GCS and it was found to have a similar if not higher prediction of mortality and poor neurological outcome in general ICU population,[7111718] traumatic brain injury patients,[19202122] stroke patients,[23] and patient admitted after cardiac arrest. [2425] Concerns have been reported regarding the accuracy of using the GCS,[2627] especially in intubated ICU patients due to the impracticality of assessing the verbal response.…”
Section: Discussionmentioning
confidence: 99%
“…For the patients with TBI, the GCS scores for severe, moderate, and mild cases were 3–7, 8–12, and 13–15 points, respectively 37, 38 . Under the AIS-ISS, the patients with MPT were classified as mild (<16), moderate (16–25) or severe (>25) 39, 40 .…”
Section: Methodsmentioning
confidence: 99%